2018 IEEE 11th International Conference on Cloud Computing (CLOUD) 2018
DOI: 10.1109/cloud.2018.00053
|View full text |Cite
|
Sign up to set email alerts
|

Specifying Semantic Interoperability between Heterogeneous Cloud Resources with the FCLOUDS Formal Language

Abstract: With the advent of cloud computing, different cloud providers with heterogeneous services and Application Programming Interfaces (APIs) have emerged. Hence, building an interoperable multi-cloud system becomes a complex task. Our idea is to design FCLOUDS framework to achieve semantic interoperability in multi-clouds, i.e., to identify the common concepts between cloud APIs and to reason over them. In this paper, we propose to take advantage of the Open Cloud Computing Interface (OCCI) standard and the Alloy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…To achieve this interoperability, the authors proposed approaches to leverage the span of IaaS solutions and approaches based on model‐driven techniques as well as vendor‐agnostic APIs . SaaS/PaaS/IaaS interoperability . This interoperability gives the clients a full control over the cloud stack from the underlying infrastructure to the platform and the deployed software.…”
Section: Research Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To achieve this interoperability, the authors proposed approaches to leverage the span of IaaS solutions and approaches based on model‐driven techniques as well as vendor‐agnostic APIs . SaaS/PaaS/IaaS interoperability . This interoperability gives the clients a full control over the cloud stack from the underlying infrastructure to the platform and the deployed software.…”
Section: Research Findings and Discussionmentioning
confidence: 99%
“…We found that some of works were not implemented, others were implemented partially, other works were only simulated and their efficiency was not proven, whereas some works are specific to one delivery model and they do not consider the other models. Another category of the works is limited to the proposed technology and it does not take into consideration the heterogeneity of the cloud resources, which causes vendor lock‐in .…”
Section: Research Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve that, we have chosen Alloy, which is a Figure 11: Projection of OCCI to EMF lightweight formal specification language based on the firstorder relational logic [43]. In a previous work, we have used Alloy to precisely define the OCCI concepts and their properties [44]. In addition, we were also able to formally analyze OCCI extensions with Alloy Analyzer, which is a solver that takes the constraints of a model and finds instances that satisfy them.…”
Section: Occiware Extension-specific Toolsmentioning
confidence: 99%